2014
DOI: 10.1016/j.jtcvs.2013.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Early and midterm outcomes of hemiarch replacement combined with stented elephant trunk in the management of acute DeBakey type I aortic dissection: Comparison with total arch replacement

Abstract: For patients with acute DeBakey type I dissection without an intimal tear in the arch, hemiarch replacement with stented elephant trunk implantation was easily performed, with satisfactory early and midterm outcomes. For these selective patients, total arch replacement with the stented elephant trunk technique did not improve the late surgical results further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 30 publications
4
34
0
1
Order By: Relevance
“…Whether or not, and to what extent the aortic arch should be replaced is an ongoing debate. Current evidence indicates that the dissection process frequently extends through the arch in most patients and that an aortic arch repair is warranted (23 (10,12,16). If the tear is localized in the root, ascending or proximal aorta, hemiarch replacement is usually adequate to save a patient life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not, and to what extent the aortic arch should be replaced is an ongoing debate. Current evidence indicates that the dissection process frequently extends through the arch in most patients and that an aortic arch repair is warranted (23 (10,12,16). If the tear is localized in the root, ascending or proximal aorta, hemiarch replacement is usually adequate to save a patient life.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with an intimal tear localized along the greater curvature close to the supra-aortic vessels, total arch replacement was performed. Concomitant stent graft was deployed in eight studies (4,10,13,17,18,(20)(21)(22). In total arch replacement with frozen elephant trunk, the deployment of stent graft was described differently between studies.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Existing studies comparing extensive and limited index repair for acute type A dissection have yielded conflicting results and recommendations, likely due to heterogeneous patient populations and diverse clinical profiles. Some studies have shown comparable mortality rates between limited and extensive index repair, whereas others have reported higher operative risk associated with extensive repair . Specifically, the reported 30‐day or in‐hospital mortality of extensive repair ranges widely from 4.7% to 29% .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the reported 30‐day or in‐hospital mortality of extensive repair ranges widely from 4.7% to 29% . In general, studies reporting lower mortality rates had younger patients (mean ages of 45, 46, and 54 years for the lowest mortality rates of 4.7%, 5.7%, and 5.9%, respectively), a known strong independent predictor of mortality . Most studies also had small numbers of patients who underwent extensive repair (range: 14–140), limiting the statistical power and generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation